Assessment of e-tendering (e-GP) process in LGED: a case study for selected offices - Joarder, Md. Saifur Rahman (BRAC University, 2016)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.